Public health bureaus: new players in health improvement in Lithuania - KALĖDIENĖ, Ramunė; ŠČEPONAVIČIUS, Audrius (Acta medica Lituanica, 2011)
Particular emphasis in the development of the public health care system in Lithuania was put on strengthening public health at the municipal level. This paper aims at investigating the possibilities and barriers of the public health reform in Lithuania byanalyzing the experience of establishing public health bureaus as the major players in public health development at the municipal level. The Lithuanian National Public Health Strategy and Action Plan have been adopted by the Government in 2006. Ministry of Health prepared legal acts and programmes that encourage local authorities to establish public health bureaus. By the end of 2010, 32 municipal Public health bureaus were set up. The core main functions of the bureaus are public health promotion, monitoring public health and child health care. The first steps of the bureaus were complicated by the lack of well-developed strategies of action and local support, as well as by financial challenges. For strengthening the position of the bureaus in society, benefits of these newly established institutions should be widely presented to the public; sustainable financing mechanisms and a focus on intersectoral cooperation, integrating public health into primary health care are needed; also, human resource development should be foreseen. In spite of the rather challenging beginning, bureaus are starting to provide means by which local governments, in partnership with the service providers, other stakeholders and the community can plan and implement public health services and programmes and play a significant role in improving the health of population.Keywords: Lithuania, public health reform, municipal level, public health bureau